Minimum effective volume of bupivacaine 0.5% for ultrasound-guided retroclavicular approach to infraclavicular brachial plexus block - Kavakli,Ali Sait (2019)
Abstract Background and objectives: The current study aimed to determine the minimum effective volume (MEV) of bupivacaine 0.5% in 50% of patients for an ultrasound-guided retroclavicular approach to infraclavicular brachial plexus block. Methods: A total of 25 adult patients who were scheduled for upper limb surgery received an ultrasound-guided retroclavicular approach to infraclavicular brachial plexus block with bupivacaine 0.5%. The needle insertion point was posterior to the clavicle and the needle was advanced from cephalad to caudal. Block success was defined as a composite score of 14 at 30 min after local anesthetic (LA) injection. The minimum effective volume in 50% of patients was determined using the Dixon-Massey up-and-down staircase method. Minimum effective volume for a successful block in 95% of the patients was also calculated using logistic regression and probit transformation. Results: The minimum effective volume of bupivacaine 0.5% resulting in successful block in 50% of patients (MEV50) according to the up-and-down staircase method was found to be 9.6 mL (95% confidence interval (CI), 5.7-13.4). The calculated minimum effective volume required for a successful block in 95% of patients (MEV95) using the probit transformation and logistic regression analysis was 23.2 mL (95% CI, 18.8-36.7). Conclusions: The MEV50 of bupivacaine 0.5% for US-guided retroclavicular approach to infraclavicular brachial plexus block was 9.6 mL and the calculated MEV95 was 23.2 mL. Future studies are required for infraclavicular brachial plexus block with different approaches, other LA agents and different concentrations of bupivacaine.